Andropogon dewetii (Poaceae: Panicoideae: Andropogoneae), a new species from South Africa - Aluoneswi C. Mashau; Lyn Fish; Francois de Wet (Kew Bulletin, 2022)

Much more give than take: South Africa as a major donor but infrequent recipient of invasive non‐native grasses - Vernon Visser; John R. U. Wilson; Lyn Fish; Carly Brown; Garry D. Cook; David M. Richardson (Global Ecology and Biogeography, 2016)
Aim Some regions donate more invaders from particular taxonomic and functional groups than they receive. We demonstrate a particularly striking donor–recipient asymmetry in invasion ecology in grasses. Specifically, we explore whether low numbers of invasive grasses in South Africa can be explained by sampling biases, introduction dynamics, species traits or invasibility of ecosystems. Location South Africa, Australia, Chile, Europe and the USA. Methods We tested for a donor–recipient asymmetry using lists of native and non‐native grasses in five regions across the globe. Then, using distribution, trait and environmental data, we tested whether regions differed in: (1) herbarium sampling effort; (2) introduction dynamics of non‐native grasses (primary uses, area of origin and minimum residence time of non‐native grasses); (3) traits of native and non‐native grasses (leaf size, height, life history, growth form, C 3 :C 4 ratio and taxonomic placement); and (4) fire frequency. Results South Africa has fewer invasive grasses, and fewer widespread invasive grasses, than other regions; while grasses native to South Africa are much more likely to be invasive elsewhere than other grasses. This asymmetry cannot be explained by sampling biases, historical trade links or minimum residence time. Rather it is likely to be due to a combination of: (1) the massive scale of the introduction of South African grasses around the world; (2) specific traits that make South African grasses successful competitors; and (3) the high fire frequency of many South African ecosystems to which many native grasses are adapted, but introduced grasses are not. Main conclusion South Africa has a high diversity of grasses that possess specific traits to cope with fire, grazing and disturbance. This makes them more competitive. Moreover, the high diversity of certain grass lineages in South Africa acts as a reservoir of potential invaders and possibly helps limit invasions in South Africa by promoting fire.

Catabrosa versus Colpodium (Poaceae: Poeae) in southern Africa, with a key to these genera and their species in Africa - Robert J. Soreng; Lyn Fish (Kew Bulletin, 2011)

Rare and infrequent southern African grasses: assessing their conservation status and understanding their biology - Nigel P. Barker; Lyn Fish (Biodiversity and Conservation, 2007)

Book reviews - Lyn Fish (Plant Systematics and Evolution, 2004)